MODAL SOSIAL DALAM PENGEMBANGAN KELOMPOK TANI JAGUNG KUNING DI DESA WAKADIA KECAMATAN WATOPUTE KABUPATEN MUNA - Putri Firsa Ayu; La Nalefo; Salahuddin Salahuddin (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
This study examines the role of social capital in enhancing yellow corn farmer groups in Wakadia Village, Watopute Subdistrict, Muna Regency. Despite abundant natural resources, Indonesia's agricultural sector faces challenges like import dependency, underscoring the need for robust farmer group development to boost productivity and food security. Social capital, encompassing trust, participation, and networks, is pivotal in fostering collaboration and resource access among farmers. The research, involved 66 yellow corn farmers selected via purposive sampling from seven farmer groups in Wakadia, a key corn production hub. Data were collected through surveys, interviews, documentation, and literature reviews, with questionnaires as the primary tool. The study employed class interval analysis to assess social capital and farmer group development, and Spearman rank correlation to evaluate their relationship. Findings indicate strong social capital (87.87%) and well-developed farmer groups (95.45%), driven by active participation, trust in group leadership, and robust networks facilitating access to technology and markets. A significant positive correlation (0.770, p=0.00) exists between social capital and group development, suggesting that higher social capital enhances group progress. Challenges include limited marketing networks, which hinder income optimization. Strengthening social capital through training, expanded partnerships, and improved facilities is recommended to sustain agricultural development.